The last twelve miles : a novel - Robuck, Erika (Sourcebooks Landmark, 2024)
During the Prohibition Rum Wars, which created a booming smuggling economy, two women masterminds—Elizebeth Friedman, the inventor of cryptanalysis working for the government, and Marie Waite (aka Spanish Marie), on the rise to rumrunner royalty to save her family—will go to any lengths to rule the Gulf Coast.